Impact of CMV Infection on Natural Killer Cell Clonal Repertoire in CMV-Naïve Rhesus Macaques - Truitt, Lauren L.; Yang, Di; Espinoza, Diego A.; Fan, Xing; Ram, Daniel R.; Moström, Matilda J.; Tran, Dollnovan; Sprehe, Lesli M.; Reeves, R. Keith; Donahue, Robert E.; Kaur, Amitinder; Dunbar, Cynthia E.; et al. (Frontiers in Immunology, 2019)
Recent functional, gene expression, and epigenetic studies have suggested the presence of a subset of mature natural killer (NK) cells responsible for maintaining NK cell memory. The lack of endogenous clonal markers in NK cells impedes understanding the genesis of these cell populations. In humans, primates, and mice, this phenotype and memory or adaptive functions have been strongly linked to cytomegalovirus or related herpes virus infections. We have used transplantation of lentivirally-barcoded autologous hematopoietic stem and progenitor cells (HSPC) to track clonal hematopoiesis in rhesus macaques and previously reported striking oligoclonal expansions of NK-biased barcoded clones within the CD56-CD16+ NK cell subpopulation, clonally distinct from ongoing output of myeloid, B cell, T cell and CD56+16- NK cells from HSPC. These CD56-CD16+ NK cell clones segregate by expression of specific KIR surface receptors, suggesting clonal expansion in reaction to specific environmental stimuli. We have now used this model to investigate the impact of rhesus CMV(RhCMV) infection on NK clonal dynamics. Following transplantation, RhCMVneg rhesus macaques display less dominant and oligoclonal NK CD16+ biased clones compared to RhCMVpos animals, however these populations of cells are still clearly present. Upon RhCMV infection, CD16+ NK cells proliferate, followed by appearance of new groups of expanded NK clones and disappearance of clones present prior to RhCMV infection. A second superinfection with RhCMV resulted in rapid viral clearance without major change in the mature NK cell clonal landscape. Our findings suggest that RhCMV is not the sole driver of clonal expansion and peripheral maintenance of mature NK cells; however, infection of macaques with this herpesvirus does result in selective expansion and persistence of specific NK cell clones, providing further information relevant to adaptive NK cells and the development of NK cell therapies.